Investigating the Prevalence of Occupational Injuries among Workers in the Informal Recycling Businesses - (:unkn) unknown (My University, 2025)
Occupation-Related Injuries (ORIs) and sicknesses continue to be major public health concerns requiring serious and urgent action. There is increasing global concern about the prevalence of occupational injuries among workers in informal recycling in developing countries especially those in sub-Saharan Africa. This is arising due partly to the poor methods of waste management. This was observed in the eastern African countries and in particular in Uganda. Solid waste recycling in Uganda landfill is done manually, which requires repeated heavy physical activities such as lifting, carrying, pulling, and pushing. In Uganda, especially in the Kiteezi landfill, the solid waste recycling process raises a lot of concern as solid waste recyclers are exposed to a number of health hazards leading to injuries. The study focused on the Kiteezi Landfill site in Wakiso District central Uganda and investigated the prevalence of occupational injuries among workers in informal recycling businesses, the factors (individual and institutional) influencing the prevalence of these injuries and the association between these factors.The study employed a quantitative research approach using a cross-sectional research design and collected data from 112 participants who were selected by stratified sampling technique. This data was collected using a structured questionnaire and was analyzed at univariate, bivariate and multivariate levels. Data was analyzed using the SPSS version 2020. Descriptive statistics (frequencies and percentages) were used to respond to objectives one and two and chi-square analysis was used to analyze the objectives of the study in order to determine the association between the organizational factors, individual factors and the prevalence of occupational injuries.The results show that the prevalence of occupational injuries was 55.4% and the only significant factor was accessibility to sanitation facilities (AOR= 0.38; 95%CI: 0.16-0.94, P = 0.05). Disrup
Keywords: African Research